The Effect of Intravenous Injection of the Water Extract of Angelica gigas Nakai on Gliosis in the Middle Cerebral Artery Occlusion Rats - Bong-Keun Song; Yong-Cheol Jeon; Sun-Ae Kim; An-Na Shim; Keemoon Seong; Eon-Jeon Lee (Korean Pharmacopuncture Institute, 2011)
Objectives: Gliosis becomes physical and mechanical barrier to axonal regeneration. Reactive gliosis induced by middle cerebral artery occlusion is involved with up-regulation of CD81 and GFAP (Glial fibrillary acidic protein). The current study is to examine the effect of the Angelica gigas Nakai(intravenous injection. 100 mg/kg twice in a day) on CD81 and GFAP of the rat in the brain after middle cerebral artery occlusion. Methods: Cerebral infarction was induced by middle cerebral artery occlusion. And after intravenous injection of water extract of Angelica gigas Nakai, the size of cerebral infarction was measured. Examination of optical microscope were also used to detect the expression of CD81 and GFAP in the brain of the rat. Results: The following results were obtained: We found that size of cerebral infarcion induced by MCAO (Middle Cerebral Artery Occlusion) in rats were decreased after intravenous injection of Angelica gigas Nakai. We injected the extract of Angelica gigas Nakai to the MCAO in rats, and the optical microscope study showed that Angelica gigas Nakai had effect on protecting the cells of hippocampus. We found that GFAP, CD81 and ERK of the brain in rats with cerebral infarction after MCAO were meaningfully decreased after intravenous injecting Angelica gigas Nakai. We found that c-Fos expression of the brain in rats with cerebral infarction after MCAO were significantly increased after intravenous injecting Angelica gigas Nakai. Conclusions: These results indicate that Angelica gigas Nakai could suppress the reactive gliosis, which disturbs the astrocyte regeneration in the brain of the rat with cerebral infarction after MCAO by controlling the expression of CD81 and GFAP. And the effect may be modulated by the up-regulation of c-Fos and ERK.